Ethanol stress responses of Kluyveromyces marxianus CCT 7735 revealed by proteomics and metabolomics analyses - Alvim, Mariana Caroline Tocantins (2017)
Non-Saccharomyces yeasts, such as Kluyveromyces marxianus, have called attention as promising strains for bioethanol production. K. marxianus displays desirable physiological characteristics for bioethanol production, such as capacity to assimilate pentoses and disaccharides beyond sucrose – present in the agro- industrial and forest residues – and thermotolerance. However, K. marxianus, contrary to Saccharomyces cerevisiae, is not tolerant to high ethanol concentrations. Moreover, its physiological responses to ethanol are not well elucidated; therefore, characterizing its physiological responses under ethanol stress is pivotal to apply this knowledge into metabolic engineering approaches to construct strains tolerant to ethanol. Thus, the aim of this work was to determine the ethanol responses of K. marxianus CCT 7735 subjected to 1 and 4 h of ethanol stress through both protein and metabolic profiles. It was observed that at 1 h of stress, although glycolytic enzymes and alcohol dehydrogenases were more abundant lactose and ethanol are not consumed by the yeast. On the other hand, at 4 h the abundance of proteins involved in carbon pathways and protein translation was reduced. In addition, there was an increase in the abundance of proteins and metabolites related to the response to oxidative and osmotic stresses, as well as to heat shock proteins. Interestingly, at 1 h of exposure to ethanol, plasma membrane ATPase was highly abundant, likely to counteract the proton motive force dissipation, which is related to the influx of protons due to increased permeability caused by ethanol. However, at 1 and 4 h of stress, respectively, the level of the metabolites trehalose, ergosterol and some amino acids reduced. Therefore, the results obtained in this study provide important information to improve the understanding of the ethanol responses displayed by K. marxianus.